Pengaruh Pemberian Pupuk Kandang Kambing Terhadap Pertumbuhan dan Hasil Tanaman Serai Wangi (Cymbopogon nardus L.) - Faisal Hadi; Novilda Elizabeth Mustamu; Hilwa Walida (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
Lemongrass (Cymbopogon nardus L.) better known as lemongrass or citronella grass or citronella grass is a type of grass from the order Gramiales which is typical of tropical areas of Asia. But this citronella plant is also a plantation crop that has the potential to be developed in Indonesia. And this research has been carried out in my home plantation area in February – April 2022. This study aims to find out the effect of fertilizing goat cage and soil on the growth and results of circular plants. The application of goat manure and soil 2:1 showed the best in increasing the number of tillers, root fresh weight, crown fresh weight, leaf fresh weight, root dry weight, shoot dry weight, plant height and number of leaf blades. then the second best results were followed by goat manure and 1:1 soil which was best in increasing the number of tillers, root fresh weight, leaf fresh weight, root dry weight, crown fresh weight, canopy dry weight, number of leaves and height. plants. And giving goat manure by giving 2:1 has a good effect on the growth and yield of citronella plants. Keywords: Goat Manure, Soil, Growth, Yield, Fragrant Lemongrass